2021
DOI: 10.24014/jnsi.v4i1.11662
|View full text |Cite
|
Sign up to set email alerts
|

Profil Literasi Sains dalam Pembelajaran IPA di Era Covid-19: Studi Kasus di Universitas Terbuka

Abstract: Literacy skills are fundamental things that students must have in facing the industrial era 4.0 to be able to meet the needs of life in various situations. Scientific literacy is the ability to understand science, communicate science, and apply science skills to solve problems. However, the scores of Indonesian students on scientific literacy abilities are still far below the international standard scores set by the OECD institution. Seeing this phenomenon, this study aims to describe the profile of students' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Science literacy skills are used to understand science and its applications. Students with science literacy skills will be able to apply their knowledge to solve problems in everyday life situations that are the ultimate goal of education [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Science literacy skills are used to understand science and its applications. Students with science literacy skills will be able to apply their knowledge to solve problems in everyday life situations that are the ultimate goal of education [2].…”
Section: Discussionmentioning
confidence: 99%
“…The basic problems found were:(1) The results of the 2018 Pisa found that Indonesia was still weak in understanding information (literacy). Literacy is one of the abilities that must be possessed by every party to understand information and reflective ideas related to scientific issues (2).…”
mentioning
confidence: 99%
“…Menurut Sugiyono (2014), metode survei digunakan untuk mendapatkan data dari populasi tertentu yang bersifat alamiah, akan tetapi dalam proses pengumpulan data dengan menyebarkan link angket, disini peneliti tidak memberikan kesempatan uji coba seperti pada eksperimen. Data kemudian dianalisis secara deskriptif untuk menghasilkan hasil penelitian pada profil subjek penelitian (Berlian et al 2021), yang ditunjukkan pada Tabel 1.…”
Section: Hasil Dan Pembahasanunclassified
“…Literasi sains peserta didik sangat penting untuk memahami lingkungan, kesehatan, ekonomi, dan masalah lain dalam masyarakat modern (Muliani et al, 2021). Literasi sains merupakan kemampuan yang digunakan dalam pengetahuan dan kecakapan ilmiah yang diantaranya dengan mengidentifikasi pertanyaan, memperoleh pengetahuan baru yang disimpulkan melalui data-data dan bukti secara ilmiah serta kesadaran memanfaatkan sains dan teknologi dalam membentuk lingkungan alam (Berlian et al, 2021;Wahyuningsih, 2021).…”
unclassified